GROWTH RATE OF DEEP-SEA OCEANIC NODULES AS INDICATED BY INERT-GAS ISOTOPES - Anufriyev G.S.; Boltenkov B.S.; Kapitonov I.N. (My University, 1989)
We investigated ferromanganese nodules primarily in order to obtain new data on the concentrations and isotopic composition of He, Ne and Ar in them; the objective was to determine whether they contained space dust and to develop a new method of determining their rates of growth. Our experiments lead to a sensitive method of determining the concentrations and isotope ratios of inert gases in nodules. We found anomalies in the isotopic compositions of helium and neon caused by accumulation of space dust that carries solar inert gases. We have proposed a new method of determining the nodule growth rate, involving measurement of the concentrations and isotope ratios of inert gases. This method is suitable for use in determining the integral (from whole-rock specimens) and differential (lawyerwise) growth rates of the nodules. The growth-rate figure of about 6 mm/103 years confirms 'rapid' nodule growth. More accurate determination of the growth rate is important for understanding the mechanisms of nodule generation and for obtaining realistic estimates of the rates of renewal of nodules under natural conditions.